Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites